Fostering Ecological Awareness from an Early Age: Integrating Environmental Education Based on the Qur’an and Hadith into Primary School Learning - Muhammad Noor; Khairil Anwar (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study explores the integration of ecological messages from the Qur’an and Hadith into primary school education as a means to foster ecological awareness and character in young learners. Amidst the global environmental crisis, early education plays a pivotal role in shaping values and behaviors that support sustainability. While environmental themes are present in Indonesia’s primary curriculum, they often lack spiritual grounding. Islam offers rich theological and ethical foundations for environmental care, such as the prohibition of corruption (fasād), the role of humans as stewards (khalifah), the importance of balance (mīzān), and commands for cleanliness. This qualitative research utilizes document analysis and content analysis to examine how these values can be contextualized in classroom practices. The findings reveal that the Qur’an and Hadith provide not only cognitive knowledge but also spiritual and moral imperatives that can be internalized through thematic learning, project-based activities, and character education. The Merdeka Curriculum and the Pancasila Student Profile Strengthening Project (P5) enable cross-subject integration of Islamic ecological values in subjects like Islamic Education, Science, Social Studies, and Bahasa Indonesia. Teachers play a crucial role as value facilitators by modeling environmentally conscious behavior rooted in Islamic teachings. Furthermore, the involvement of families and communities enhances the educational impact, reinforcing that caring for the environment is an act of worship. This research contributes to the development of spiritually grounded environmental education strategies and highlights the potential of Islamic values to promote sustainable living from an early age.